Jurnal Ulunnuha - UIN Imam Bonjol Padang. Fakultas Ushuluddin Dan Studi Agama; Asosiasi Ilmu al-Qur'an dan Tafsir se-Indonesia (Ushuluddin Faculty, The State Islamic University Imam Bonjol Padang in collaboration with Asosiasi Ilmu al-Qur'an dan Tafsir (AIAT) se-Indonesia, 2012)
Scientific journal focusing on the study of the Qur'an and Hadith.
Keywords: Qurʼan : Periodicals; Qurʼan; Hadith : Periodicals; Hadith